2014
DOI: 10.1038/labinvest.2014.73
|View full text |Cite
|
Sign up to set email alerts
|

VSIG4 expression on macrophages facilitates lung cancer development

Abstract: Tumor-associated macrophages are a prominent component of lung cancer stroma and contribute to tumor progression. The protein V-set and Ig domain-containing 4 (VSIG4), a novel B7 family-related macrophage protein that has the capacity to inhibit T-cell activation, has a potential role in the development of lung cancer. In this study, 10 human non-small-cell lung cancer specimens were collected and immunohistochemically analyzed for VSIG4 expression. Results showed massive VSIG4 þ cell infiltration throughout t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 34 publications
3
64
0
Order By: Relevance
“…To date, in vitro and in vivo studies have consistently implicated VSIG4 as a receptor of complement C3 on the surface of macrophages playing a vital role in phagocytosis and the clearance of pathogens in the circulation (Helmy et al, 2006;Vogt et al, 2006). Most studies have focused on the function of VSIG4 in phagocytosis (Gorgani et al, 2011;Broadley et al, 2016;Zeng et al, 2016;Nagre et al, 2018), although several recent studies have found that VSIG4 is associated with tumour progression (Liao et al, 2014;Xu et al, 2015;Byun et al, 2017). Normally, VSIG4 is expressed on resting macrophages and expression is lost upon activation, and VSIG4 hi macrophages plays an anti-inflammatory and immunosuppressive role in vivo (Vogt et al, 2006;Irvine et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To date, in vitro and in vivo studies have consistently implicated VSIG4 as a receptor of complement C3 on the surface of macrophages playing a vital role in phagocytosis and the clearance of pathogens in the circulation (Helmy et al, 2006;Vogt et al, 2006). Most studies have focused on the function of VSIG4 in phagocytosis (Gorgani et al, 2011;Broadley et al, 2016;Zeng et al, 2016;Nagre et al, 2018), although several recent studies have found that VSIG4 is associated with tumour progression (Liao et al, 2014;Xu et al, 2015;Byun et al, 2017). Normally, VSIG4 is expressed on resting macrophages and expression is lost upon activation, and VSIG4 hi macrophages plays an anti-inflammatory and immunosuppressive role in vivo (Vogt et al, 2006;Irvine et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…45 VSIG4 molecules appear to be expressed on the surface of resident macrophages in peripheral tissues including the liver, and they disappear after macrophage activation. 21 Consequently, immature macrophages in local tissues control unwanted immune responses by suppressing T cell activation via VSIG4.…”
Section: Discussionmentioning
confidence: 99%
“…These results support the role of wild-type CALR in the regulation of physiological hematopoiesis enhancing differentiation toward the erythroid and MK lineages. Furthermore, our GEP data pointed out the upregulation of several proinflammatory genes, such as the chemokines CCL2 [25], CCL3 [26], and CXCL5 [27], and cytokines like IL8 [27], and cancer-related markers already described in hematological neoplasms, such as EMP1 [30], VSIG4 [31], and LEP [32].…”
Section: Discussionmentioning
confidence: 99%
“…Functional analysis by means of Ingenuity Pathway analysis software (IPA, version 8.6; Ingenuity Systems, Redwood City, CA, www.ingenuity.com) identified several categories of DEGs, such as platelet aggregation, proinflammation genes, erythrocyte differentiation, and several cancer markers already known in both solid and hematological neoplasms. In particular, among upregulated genes, we found genes involved in platelet activation and aggregation, such as SGK1 [21], CD9 [22], FN1 [23], and THBS1 [24]; genes involved in proinflammatory mechanisms such as chemokines CCL2 [25], CCL3 [26], and CXCL5 [27] and cytokines like IL8 [27]; genes involved in erythrocyte differentiation such as RHCE [28] and HBZ [29]; and several cancer markers already known in both solid and hematological malignancies such as EMP1 [30], VSIG4 [31], and LEP [32] ( Fig. 3B and Supplemntary Fig.…”
Section: Gene Expression Profile Of Calr-overexpressing Cd34 + Cellsmentioning
confidence: 99%